2021
DOI: 10.1161/strokeaha.120.032054
|View full text |Cite
|
Sign up to set email alerts
|

PRESERVE: Randomized Trial of Intensive Versus Standard Blood Pressure Control in Small Vessel Disease

Abstract: Background and Purpose: In cerebral small vessel disease, cerebral blood flow and autoregulation are impaired and therefore excessive blood pressure reduction could possibly accelerate white matter damage and worsen outcome. The trial determined, in severe symptomatic cerebral small vessel disease, whether intensive blood pressure lowering resulted in progression of white matter damage assessed using diffusion tensor imaging. Methods: Randomized, parall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 26 publications
1
33
0
Order By: Relevance
“…However, for a non‐stroke cohort, the recent SPRINT‐MIND study suggested intensive blood pressure‐lowering to a systolic of 120 mmHg, compared with standard lowering to 140 mmHg, was associated with a reduced incidence of mild cognitive decline and the combined endpoint of MCI and dementia [199]. There has been concern that intensive blood pressure‐lowering may have risks in people living with extensive small vessel disease and impaired cerebral autoregulation, but the recent PRESERVE study showed no reduction in cerebral blood flow, increased white matter damage, or difference on cognition associated with blood pressure‐lowering to 125 mmHg compared with 140 mmHg [200]. Consistent with this finding, the SPS3 cognitive substudy reported no adverse consequences of lowering blood pressure to this level [23].…”
Section: Discussionmentioning
confidence: 99%
“…However, for a non‐stroke cohort, the recent SPRINT‐MIND study suggested intensive blood pressure‐lowering to a systolic of 120 mmHg, compared with standard lowering to 140 mmHg, was associated with a reduced incidence of mild cognitive decline and the combined endpoint of MCI and dementia [199]. There has been concern that intensive blood pressure‐lowering may have risks in people living with extensive small vessel disease and impaired cerebral autoregulation, but the recent PRESERVE study showed no reduction in cerebral blood flow, increased white matter damage, or difference on cognition associated with blood pressure‐lowering to 125 mmHg compared with 140 mmHg [200]. Consistent with this finding, the SPS3 cognitive substudy reported no adverse consequences of lowering blood pressure to this level [23].…”
Section: Discussionmentioning
confidence: 99%
“…33 Furthermore, In a randomized controlled trial of standard (systolic=130–140 mm Hg; N=56) or intensive (systolic<125 mm Hg; N=55) SBP lowering, intensive SBP had no significant effects on white matter integrity in patients with small vessel disease and history of lacunar stroke suggesting the safety of BP lowering in those with severe small vessel disease of the brain. 36 Hence, low baseline DBP should not be an impediment to guidelines 8 recommended SBP goal of<130 mm Hg in persons with previous history of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…After intensive blood pressure lowering in severe cSVD patients, no difference in microstructural integrity evaluated with DTI was found, suggesting that blood pressure control is a protective factor for cSVD development and that DTI is a sensitive marker for evaluating such a therapeutic strategy 123 …”
Section: Resultsmentioning
confidence: 92%
“…122 After intensive blood pressure lowering in severe cSVD patients, no difference in microstructural integrity evaluated with DTI was found, suggesting that blood pressure control is a protective factor for cSVD development and that DTI is a sensitive marker for evaluating such a therapeutic strategy. 123 Finally, depression in the setting of cSVD has also been the subject of investigation. Depression in cSVD patients has been associated with reduced WM integrity measured through FA.…”
Section: Complications and Outcomes Of Csvd Associated With Dti-deriv...mentioning
confidence: 99%